High-field quantum transport in nanostructured devices and integrated circuits - K. Arora, Vijay (Faculty of Electric Engieering, 2008)
The application of quantum waves as carriers of information was investigated in a number of activities involving FKE staff, Ph. D. scholars, and PSM students (all named as members of the effective teams in the papers listed below). As outlined in the project design, the project activities transferred technical know-how to staff and students of UTM working in crossdisciplinary teams. It was a splendid display of innovations through teamwork in the true spirit of the Principle of Complementarities, each team player doing what was best for him. The investigations resulted in 5 journal papers with 6 papers in the pipeline being reviewed for possible publication and more to follow. The paper in the Applied Physics Letters was given Premium Award for the most outstanding paper with the highest impact factor at the Majlis Anugerah Citra Karisma held on May 15, 2008, Dewan Sultan Iskandar, UTM. A number of papers were published in conference proceedings. The knowledge obtained was disseminated through seminars and professional talks under the IEEE Distinguished Lectures Program and also at regional and international conferences. The project outcome is showing its impact on the international scientific community, on students through mentoring program on research-based education, on the FKE that is considering nanotechnology as one of its strengths, and on UTM reputation through its international visibility that may allow it to be viewed as a global educational entity.